The Influence of Online Customer Review and Influencer Review on Purchase Intention of Somethinc Products on Tiktok Social Commerce : (Studi on Tiktok Users in Bandar Lampung) - Dera Nandia; Yuniarti Fihartini; Mutiasari Nur Wulan (International Forum of Researchers and Lecturers, 2025)
The rapid advancement of the internet and social media has led to the emergence of social commerce, which integrates e-commerce with social media platforms. Reviews, as a form of electronic word-of-mouth (e-WOM), have become a key information source relied on by consumers in social commerce. However, the growing presence of buzzers and paid endorsements producing fake reviews has weakened the relevance and trustworthiness of e-WOM, including both online customer reviews and influencer reviews. This study aims to examine the impact of online customer reviews and influencer reviews on the purchase intention of Somethinc products on TikTok’s social commerce platform. The research adopts a quantitative approach with purposive sampling, involving 120 TikTok users in Bandar Lampung as respondents. Data were analyzed using multiple linear regression with SPSS 27 software. The findings reveal that both online customer reviews and influencer reviews significantly and positively influence purchase intention. These results suggest that exposure to online customer and influencer reviews can enhance consumers’ purchase intention toward Somethinc products on TikTok social commerce.